Effect of process temperature on morphology of CNTs grown in a vertically fluidized bed reactor with Fe 2 O 3 /Al 2 O 3 catalyst - Shukrullah, S. (American Institute of Physics Inc., 2015)
Carbon nanotubes (CNTs) are one of the most researched materials due to their exceptional mechanical and electrical properties. Among the various techniques, catalytic chemical vapor deposition in a fluidized bed reactor is the most promising technique for bulk production of CNTs. To meet the demand of good quality along with the bulk production of CNTs, the effect of reaction temperature on the micro structures, morphology, diameter, quality and quantity of CNTs was investigated in these studies. CNTs were synthesized at process temperature ranging from 700-850Â°C by catalytic decomposition of C 2 H 4 on Fe 2 O 3 /Al 2 O 3 catalyst a vertical fluidized bed reactor. The microstructures of the grown CNTs at different reaction temperatures were investigated by using scanning electron microscope. The results of this study depicted a positive correlation between the average diameter of CNTs and reaction temperature. Narrow diameters (35â¼40 nm) of CNTs with fewer defects were found at the low and mild temperatures, in particular 800Â°C. At this temperature, a dynamic equilibrium between the rate of C 2 H 4 decomposition and CNTs quantity was found due to maximum carbon diffusion over catalyst. The CNTs produced with Fe 2 O 3 /Al 2 O 3 catalyst wer e also exhibiting high quality with relatively small mean outer diameter and fewer surface defects. Â© 2015 AIP Publishing LLC.